Deposition and characterization of polycrystalline diamond coated on silicon nitride and tungsten carbide using microwave plasma assisted chemical vapour deposition technique - Agung Purniawan, Agung Purniawan (2008)
Diamond (sp3) is a unique engineering material, due to its superior combination of physical, optical and chemical properties and thus it is possible to take advantage of these properties in many engineering applications for which high hardness, high resistance to corrosion and erosion is required. In the present study, deposition and characterization of polycrystalline diamond coated on silicon nitride (Si3N4) and tungsten carbide (WC) substrates using microwave plasma assisted chemical vapor deposition (MPACVD) technique were investigated. The pretreatment processes were conducted on the substrate materials to enhance adhesion and nucleation of diamond namely cleaning, chemical etching (for WC substrate to remove cobalt content from the substrate surface) and diamond seeding. Total gas flow rate and deposition time were kept constant at 200 sccm and for 7 hours respectively. Variable deposition parameters used were %CH4 concentration, microwave power, and chamber pressure at 1 – 3%CH4, 2.75 – 3.75kW, and 40 – 60 torr respectively. Microstructure, morphology and surface roughness were investigated by optical microscopy, scanning electron microscopy and atomic force microscopy. Phase analysis, residual stress and diamond quality were determined by X-ray diffraction and Raman spectra. Coating adhesion and wear resistance was determined using Rockwell hardness indenter and pin-on-disk tribometer. The results show that H2O2:HNO3:H2O reagent and 10 minutes etching time was found to be the optimum parameter on cobalt removal from WC substrate. It was also observed that increase in %CH4 concentration enhance diamond nucleation and growth, increase diamond coating thickness and reduce surface roughness. Microwave power and chamber pressure increase the density of diamond, diamond quality and transform diamond facet from cauliflower to octahedral structure. Raman spectra results show that all residual stresses are compressive and pin-on-disk results indicate that octahedral diamond structure has better coating adhesion than cauliflower structure.